2021
DOI: 10.1108/aeat-01-2021-0005
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive rapid neural observer-based sensors fault diagnosis and reconstruction of quadrotor unmanned aerial vehicle

Abstract: Purpose The objective of this research is to investigate various neural network (NN) observer techniques for sensors fault identification and diagnosis of nonlinear system in consideration of numerous faults, failures, uncertainties and disturbances. For the importunity of increasing the faults diagnosis and reconstruction preciseness, a new technique is used for modifying the weight parameters of NNs without enhancement of computational complexities. Design/methodology/approach Various techniques such as ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Biddle and Fallah (2021) have introduced an identification approach for faults occurring simultaneously at multiple sensors in autonomous vehicle controllers via multiclass SVM models. Taimoor et al (2021) have proposed using adaptive radial basis functions for sensor fault identification or quadrotor unmanned aerial vehicles. Aiming to identify sensor faults of gas turbine engines, Zhu et al (2020) have introduced a residual-based scheme to identify single and simultaneous sensor faults occurring at different sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Biddle and Fallah (2021) have introduced an identification approach for faults occurring simultaneously at multiple sensors in autonomous vehicle controllers via multiclass SVM models. Taimoor et al (2021) have proposed using adaptive radial basis functions for sensor fault identification or quadrotor unmanned aerial vehicles. Aiming to identify sensor faults of gas turbine engines, Zhu et al (2020) have introduced a residual-based scheme to identify single and simultaneous sensor faults occurring at different sensors.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of unmanned aerial vehicles (UAVs), the problem of ensuring reliability and control (Abbaspour * Corresponding author et al, 2018;Hamadi et al, 2020;Altan and Hacıoglu, 2020;Prochazka and Stomberg, 2020;Taimoor et al, 2021) is particularly important because they are characterized by high dynamics and functioning in varying conditions with a large amount of disturbances. In order to ensure the reliable operation of a UAV, various methods of fault detection and estimation of the remaining useful life of the vehicle components can be used (Zhang et al, 2021;Sadhu et al, 2020;Camci et al, 2019;Rodrigues et al, 2018;Petritoli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…An overview of FTC methods can be found the works of Veremey (2021), Habibi et al (2019, Li et al (2019), Hamdi et al (2021 and Witczak (2014). Moreover, interesting theoretical studies and practical applications of active FTC methods in the case of faulty sensors (Manohar and Das, 2020;Wang, 2020;Azzoug et al, 2021;Taimoor et al, 2021) and actuators (Hamadi et al, 2020;Prochazka and Stomberg, 2020;Yu et al, 2021;Liu et al, 2021) can also be found.…”
Section: Introductionmentioning
confidence: 99%
“…Any failure in these sensors can lead to severe losses and human injuries due to the presence of faults and disturbances (Taimoor and Aijun, 2020). Since the sensor faults cannot be avoided in practical conditions which may result in the system’s performance degradation, quick diagnosis of such faults are greatly appreciated in making the flight operations of UAV reliable and safe (Taimoor et al , 2021). Once the faults are identified, necessary actions can be taken to cancel out their effect to guarantee a successful flight mission.…”
Section: Introductionmentioning
confidence: 99%